Odpowiedzi

2010-03-12T15:14:14+01:00
A) 2x+6=10 2x=10-6 2x=4/:2 x=2
b) 3x-3+2=8 3x=8+3-2 3x=9/:3 x=3
c) 26-2x-9=1 -2x=1-26+9 -2x= -16/:(-2) x=8
d) 3-3x+2=-7 -3x=-7-3-2 -3x=-12/:(-3) x=4
e) 3x+9=2x+8+x+1 0x=8+1-9 0=0
f) 12x+8+10x+15=-2x-13 24x=-13-8-15 24x=-36/:24 x=-1,5
g) 4x-8-2x+8=5x+5-3x 2x-8+8=5x-3x+5 2x=2x+5 2x-2x=5 0=5
h) 2x-8=4x-2+6x+6 -8x=-4/:(-8) x=0.5
2 5 2
2010-03-12T15:18:48+01:00
A)2(x+3) = 10
2x+6=10
2x=10-6
2x=4 /podzielić 2
x= 2

b)3(x-1)+2 = 8
3x-3+2=8
3x=8-2+3
3x=9 /:3
x=3

c)2(13-x)-9 = 1
26-2x-9=1
2x=1-26+9
2x=-16 /:2
x=-8

d)3(1-x)+2 = -7
3-3x+2= -7
-3x=-7-3-2
-3x=-12 /: -3
x= 4

e)3(x+3) = 2(x+4)+x+1
3x+9=2x+8+x+1
3x-2x-x=8+1-9
0=0

f)4(3x+2)+5(2x+3) = -(2x+13)
12x+8+10x+15=-2x-13
12x+10x+2x=-13 - 8-15
24x=-36 /:24
x=-36/24
x=-9/6
x=- 3/2
==1 i jedna druga

g)4(x-2)-2(x-4) = 5(x+1)-3x
4x-8-2x+8=5x+5-3x
4x-2x-5x+3x=5+8-8
-3x=5 /:-3
x= -5/3
x=1 i dwie trzecie


h)2(x-4) = 2(2x-1)+6(x+1)
2x-8=4x-2+6x+6
2x-4x-6x=-2+6+8
-8x=12 /:-8
x=-12/8
x=-3/2
x=-1ijedna druga
2 3 2
Najlepsza Odpowiedź!
2010-03-12T15:21:33+01:00
A)2(x+3) = 10
2x+6=10
2x=10-6
2x=4/:2
x=2

b)3(x-1)+2 = 8
3x-3+2=8
3x=8-2+3
3x=9/:3
x=3

c)2(13-x)-9 = 1
26-2x-9=1
-2x=1+9-26
-2x=-16/:(-2)
x=8

d)3(1-x)+2 = -7
3-3x+2=-7
-3x=-7-2-3
-3x=-12/:(-3)
x=4

e)3(x+3) = 2(x+4)+x+1
3x+9=2x+8+x+1
3x-2x-x=1+8-9
0=0

f)4(3x+2)+5(2x+3) = -(2x+13)
12x+8+10x+15=-2x-13
12x+10x+2x=-13-15-8
24x=-36/:24
x=-36/24
x=-1 cala i 12/24
x=-1cala i 3/6
x=-1cala i 1/2


g)4(x-2)-2(x-4) = 5(x+1)-3x
4x-8-2x+8=5x+5-3x
4x-2x-5x+3x=5-8+8
0=5 - równanie sprzeczne = trzeba przekreślić

h)2(x-4) = 2(2x-1)+6(x+1)
2x-8=4x-2+6x+6
2x-4x-6x=6+8-2
-8x=12/:(-8)
x=-12/8
x=-1 cala i 4/8
2 5 2